Annotated checklist of the European Dacnusini and the Dapsilarthra genus group of the Alysiini (Hymenoptera: Braconidae, Alysiinae) - Godfray, HCJ; van Achterberg, C (Magnolia Press, 2024)
An annotated checklist of the European Dacnusini (426 species) and the Dapsilarthra genus group of the Alysiini (16 species) (Hymenoptera: Braconidae, Alysiinae) is provided. In addition to a species list with synonymy, further details are given of: (i) intrageneric groupings; (ii) a reference to each species’ treatment in the unindexed and multipart major revisions of Nixon & Griffith as well as the long keys of Tobias; (iii) a hypothesis about host range for the 60% of species which have been reared, and the evidence upon which it is based; (iv) whether a DNA barcode sequence is available (30% of species); (v) for species published after Griffiths’ revision a reference to similar species; (vi) any further relevant notes. One new synonym is established: Chorebus luzulae Griffiths syn. nov. is synonymised with Chorebus aphantus Marshall. Mesocrina Förster is excluded from the Dapsilartha genus group and whether Grandia Goidanich and Lodbrokia Hedqvist are in the Dacnusini is considered uncertain.